2021
DOI: 10.1021/acsbiomaterials.1c00251
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Endothelialization by Topographical Features Is Mediated by PTP1B-Dependent Endothelial Adherens Junctions Remodeling

Abstract: Endothelial Cells (ECs) form cohesive cellular lining of the vasculature and play essential roles in both developmental processes and pathological conditions. Collective migration and proliferation of endothelial cells (ECs) are key processes underlying endothelialization of vessels as well as vascular graft, but the complex interplay of mechanical and biochemical signals regulating these processes are still not fully elucidated. While surface topography and biochemical modifications have been used to enhance … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 98 publications
0
9
0
Order By: Relevance
“…As it has been observed that micro-structured surfaces with gratings can enhance EC alignment and improve the integrity of cell-to-cell junctions ( 15 ), we produced surfaces with an anisotropic topography with gratings of 1 μm width and height ( Supplementary Figure 4 ) and tested under static conditions whether these topographies have a positive impact on the biomechanical properties of both non-senescent and senescent HUVECs. At first, we investigated the cell anchoring to the surface (flat vs. grating) by imaging paxillin and its phosphorylated form as important regulators of FA assembly and disassembly ( Figures 3A,B ) ( 30 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As it has been observed that micro-structured surfaces with gratings can enhance EC alignment and improve the integrity of cell-to-cell junctions ( 15 ), we produced surfaces with an anisotropic topography with gratings of 1 μm width and height ( Supplementary Figure 4 ) and tested under static conditions whether these topographies have a positive impact on the biomechanical properties of both non-senescent and senescent HUVECs. At first, we investigated the cell anchoring to the surface (flat vs. grating) by imaging paxillin and its phosphorylated form as important regulators of FA assembly and disassembly ( Figures 3A,B ) ( 30 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, Gorji et al showed that ECs cultivated under static conditions on a micro-scale grating topography respond similarly to the AJs and actin cytoskeleton remodeling that occurs under laminar flow conditions. In particular, EC cultivation on gratings promote their shape elongation due to F-actin stress fibers and the formation of linear VEC AJs, as shown by the increase in EC aspect ratio and tortuosity index, respectively ( 46 ). In line with these results, Franco et al demonstrated a 40% increase in endothelial spreading on gratings with groove width and depth of 1 μm due to focal adhesion kinase (FAK) activation, as well as enhanced FA maturation and myosin-II dependent cell contractility ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All in all, given that the number of morphological clusters observed are in the range of several, it is hopeful that the underlying biochemical signalling differences that underlie such heterogeneity will be tractable. In parallel to dissecting the origin of morphological heterogeneity, further experimentation could also explore the contribution of ECM density, substrate rigidity or viscoelastic properties, as well as spatial organization both at the micro-and nano-scale, in contributing to the morphological profiles of the cells 50,51 .…”
Section: Discussionmentioning
confidence: 99%